Hearing loss can also be seen in patients with nonradiographic axial spondyloarthropathies as well as radiographic axial spondyloarthropathies - Hanife Çağlar Yağcı; İlker Yağcı and Osman İlkay Özdamar and Cansu Tosyalı Salman and Özlem Ertuğrul (Archives of Rheumatology, 2023)
Objectives: Hearing loss has been described in patients with radiographic axial spondyloarthropathies (R-AxSpA) but has not been studied in patients with non-radiographic axial spondyloarthropathies (NR-AxSpA); accordingly, the aim of the study was to compare hearing loss in patients with NR-AxSpA, R-AxSpA, and healthy individuals. Patients and methods: This cross-sectional observational study was conducted with 68 participants (30 males, 38 females; mean age: 39.8±7.4 years) between March 2021 and March 2022. Of the participants, 16 were patients with NR-AxSpA, 15 were patients with R-AxSpA, and 37 were healthy controls. Disease activity and radiological and audiological features were analyzed. The audiological assessment included pure-tone audiometric tests at octave frequencies of 250 to 8000 Hz and transient evoked otoacoustic emissions. Results: Hearing loss was found in three (8%) in the healthy group, five (31.3%) in the NR-AxSpA group, and 10 (66.7%) in the R-AxSpA group. The chi-square analysis showed a statistical significance (p=0.001). Values of audiometric tests yielded significant differences between the control and R-AxSpA group and also the control and NR-AxSpA group. For the air conduction studies, the statistical significance began at 1000 Hz in the R-AxSpA group. It was found that in the NR-AxSpA group, the statistical difference started in higher frequencies. The bone conduction audiometric studies were similar to air conduction studies. Transient evoked otoacoustic emission studies showed that the R-AxSpA group was significantly affected compared to the control and NR-AxSpA groups. There was no statistical difference between the control and NR-AxSpA groups. Conclusion: Both NR-AxSpA and R-AxSpA patients had hearing loss; however, in pure-tone audiometric tests, the abnormalities began in lower frequencies in the R-AxSpA group than in the NR-AxSpA group.